2017
DOI: 10.1590/0101-60830000000141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium nitroprusside in the prevention of schizophrenia-like symptoms induced by ketamine – A translational double-blind study

Abstract: Background: Recent evidence has shown improvements in schizophrenia symptoms after the infusion of sodium nitroprusside (SNP), a nitric oxide (NO) donor. In the rat model of schizophrenia using ketamine injection, pretreatment with SNP seems to prevent behavioral changes associated with positive symptoms for up to one week. Objective: We investigated whether SNP would have preventative effects on psychogenic symptoms induced by ketamine in healthy subjects. Methods: Healthy subjects (N = 38) were assigned to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In healthy subjects, SNP was able to prevent psychogenic symptoms induced by ketamine. 111 Other studies by the same group in rats showed that a single dose of SNP prevented psychosis-like behaviour produced by ketamine 112 and that SNP treatment more consistently decreased ketamine-induced behaviours than other NO-related compounds. 113 Thus, in these SNP studies, basic science research findings in animal models were translated to the clinical situation, then reverse translated back to animal models to further investigate mechanisms of action and other potential therapies.…”
Section: Drug-induced Modelsmentioning
confidence: 96%
“…In healthy subjects, SNP was able to prevent psychogenic symptoms induced by ketamine. 111 Other studies by the same group in rats showed that a single dose of SNP prevented psychosis-like behaviour produced by ketamine 112 and that SNP treatment more consistently decreased ketamine-induced behaviours than other NO-related compounds. 113 Thus, in these SNP studies, basic science research findings in animal models were translated to the clinical situation, then reverse translated back to animal models to further investigate mechanisms of action and other potential therapies.…”
Section: Drug-induced Modelsmentioning
confidence: 96%
“…Improvement in psychotic symptoms was observed in patients with schizophrenia treated with SNP (Hallak et al, 2013) although other studies failed to replicate this finding (Brown et al, 2019; Stone et al, 2016). Recently Rezende et al (Rezende et al, 2017) found that SNP may prevent some psychiatric symptoms, measured with the Brief Psychiatric Rating Scale (BPRS), induced by ketamine administration in healthy controls.…”
Section: Introductionmentioning
confidence: 99%